Community Empowerment in Reducing Stunting through the Canting Gula Mojo Program in Mojokerto City - Wafa, Ali; Pramudiana, Ika Devy; Fatah, Zainal; Anwar, M. Khairul (Side: Scientific Development Journal, 2024)
This study focuses on the challenges and efforts of community empowerment in reducing stunting rates through the Canting Gula Mojo Program in Mojokerto City. The primary issues addressed include the high prevalence of stunting in certain areas with diverse socioeconomic conditions, limited access to nutritional resources, and low awareness among families regarding the importance of proper childcare and balanced nutrition. Drawing on Jim Ife's (1997) theory of community empowerment, this research analyzes how the provision of resources, opportunities, knowledge, and skills can enhance community capabilities in addressing these challenges. The program aims to empower the community through education, distribution of nutritional resources, and capacity building for health cadres to achieve sustainable stunting reduction targets. This study employs a qualitative research method, utilizing primary data from in-depth interviews with policymakers, health cadres, and beneficiaries, alongside secondary data from official reports by the Mojokerto City Health Office. The findings reveal that the Canting Gula Mojo Program increased community participation by up to 85% in 2023, with 80% of the target audience improving their understanding of the importance of balanced nutrition. Furthermore, the program successfully reduced stunting rates to 2.26% in the same year, marking a significant decrease compared to previous years. This achievement was facilitated by providing skill training to health cadres, distributing high-protein foods, and monitoring children's growth using anthropometric kits. The study concludes that community empowerment through the Canting Gula Mojo Program is not only effective in enhancing individual and community capacities but also serves as an impactful innovation in stunting prevention efforts. Nevertheless, challenges such as budget constraints, access disparities, and the need for more detailed data mapping continue to influence program implementation. Consequently, this research recommends strengthening cross-sectoral collaboration, more targeted budget allocation, and optimizing technology for data mapping and equitable resource distribution. The program's framework can also be adapted and replicated in other regions to align with the national strategy of achieving "zero new stunting" by 2024.